2021
DOI: 10.3390/molecules26227022
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Deep Eutectic Systems towards the Treatment of Tuberculosis and Colorectal Cancer: Opportunities and Challenges

Abstract: What if a new technology based on therapeutic deep eutectic systems would disrupt the current treatment of major economic and socially burden diseases? The classical definition of eutectic systems is that they are the combination of two or more compounds that interact via hydrogen bonds, from which results a melting temperature depression in comparison with that of its individual components. Therapeutic deep eutectic systems are defined as eutectic systems in which at least one of the individual components is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…DESs have been described as compounds with negligible toxicity, good biodegradability and non-volatile. [20][21][22][23] Nevertheless, it should be borne in mind that these properties are not general and depend on the specific DES and its constituents and composition. A large proportion of research has been focused on the application of DESs, with several works showing the use of DESs for the extraction and storage of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…DESs have been described as compounds with negligible toxicity, good biodegradability and non-volatile. [20][21][22][23] Nevertheless, it should be borne in mind that these properties are not general and depend on the specific DES and its constituents and composition. A large proportion of research has been focused on the application of DESs, with several works showing the use of DESs for the extraction and storage of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As of recent, a few classes of DESs have been identified, which include natural deep eutectic solvents, as the name suggests, components used for the synthesis of natural deep eutectic solvents are obtained from natural sources such as sugar, amino acids, and organic acids [ 108 , 109 ]. Therapeutic deep eutectic solvents are eutectic mixtures containing APIs as part of the formulation [ 110 ]. DES possesses excellent properties that complement some of the obstacles of existing solvents, especially in the area of drug delivery.…”
Section: Chemical Enhancersmentioning
confidence: 99%
“…Even a different mechanism of action is followed by the THEDESs compared to the isolated ibuprofen and limonene, but their advantages for cancer therapy are preserved [31]. Notably, in a review, Oliveira et al suggested to understand the cytotoxicity process of THEDESs when affecting different kinds of cell lines, malignant and non-malignant, in order to take advantage of this knowledge to design proper therapies for specific cancer types, such as colorectal cancer [59]. Later on, Pereira et al evaluated the usefulness of different THEDES including terpenes and nonsteroidal anti-inflammatory drugs.…”
Section: Cell Lines 21 Cell Viabilitymentioning
confidence: 99%